Water management for sustainable agricultural intensification and smallholder resilience in Sub-Saharan Africa - Cofie, Olufunke O.; Amede, Tilahun (Elsevier, 2015)
Water management strategies and allocation policies that support agricultural intensification across agro-ecological zones and hydrologic basins are required for building resilient agrarian communities in sub-Saharan Africa.We provide an overview of the research and investments needed to enhance agriculture in the region, with a focus on technology and institutions, while describing opportunities for improving rainfed crop production.We discuss a range of water management practices in three river basins that were part of the Challenge Program onWater and Food research on Basin Development Challenges from 2009 to 2013. Our main message is that technical and institutional innovations in water management are required for creating and sustaining resilient agrarian communities in sub-Saharan Africa. Such innovations are best designed and implemented in consultations involving researchers, households, investors, and other participants with a management or regulatory responsibility. It is in this collaborative spirit that we introduce this Special Issue of Water Resources and Rural Development, in which several authors present results of studies on agricultural water management in the region, with recommendations for better planning and implementation of interventions to benefit smallholder farmers.